PENGARUH LAMA PERIODE KERING DAN INTENSITAS CURAH HUJAN TERHADAP PENETASAN BELALANG KEMBARA (LOCUSTA MIGRATORIA MANILENSIS MEYEN) - Hamim Sudarsono . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2008)
Effect of Dry Period and Rainfall Intensity on Emergence of the Migratory Locust (Locusta migratoria manilensis Meyen). Dry period and rainfall intensity were simulated experimentally to determine their effects on nymph emergence of the migratory locust (Locusta migratoria manilensis Meyen) (Orthoptera: Acrididae). The experiment was conducted in a factorial set up with two factors, i.e. dry periods (1, 2, 4, 8, and 12 week interval of watering) and rainfall intensity (80, 140, 200, and 260 mm/month). Locust nymphal emergence and time required to emerge after the watering were recorded and analyzed. Results of the experiment indicated that dry periods and rainfall levels affected nymphal emergence of the migratory locust. Interaction between dry periods and rainfall levels, however, were statistically not significant (F-value = 0,69 and P-value = 0,7526). Nymphal emergences of L. m. manilensis tended to be higher on soils that were watered less frequently. Similarly, locust emergences were also higher for the soil with lower rainfall intensity (received less amount of watering). At the 80 mm/month rainfall level, 20 – 105,5 days period (egg incubation period) were required before the locust emergence. Incubation period of the eggs was significantly higher as the breeding media (soil) were watered less frequently. On the other hand, time required for the egg to emerge as nymphs was relatively similar regardless of the dry period levels. All eggs emerged 14 – 15,5 days after watering.